IMPLEMENTATION OF SUMMATIVE ASSESSMENT IN PBL TUTORIALS: CULTURAL PERSPECTIVES - Umatul Khoiriyah; Chris Roberts (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Problem-based learning was developed firstly in western country which is dominated by western culture. The benefits of PBL implementaion in Eastern culture such as Asia have been studied. Many  innovations have been developed to optimise the advantages of PBL on students learning in Asian countries. Faculty of Medicine Islamic University of Indonesia (FM IUI) has made an innovation by applying summative assessment in PBL tutorials. This study aims to evaluate the positive and negative effects of summative assessment in PBL tutorials based on a cultural perspective and to know whether this inovation could support students learning in PBL tutorials. Method: The research was conducted qualitatively through semi-structure interview among 10 students and tutors of FM IUI , who have at least one year experience in PBL tutorials. Data was analysed thematically using Hofstede’s cultural dimension. Results: Ten themes that were distributed into 4 cultural dimensions were captured from the data. It consisted of Power distance ( 2 themes), uncertainty avoidance (3 themes), Individualism vs collectivism ( 2 themes), short orientation vs long orientation ( 2 themes). Summative assessment were able to stimulate student to participate actively in tutorial, to have willingness conducting self-improvement and the need of feedback from tutor. On the other hand, this assessment induced the students to be a score oriented. It also reduced group harmonisation.Supporting factors such as case design, tutor capability and students’ understanding about PBL need to be considered. Conclusion: Summative assessment in PBL tutorials has both positive and negative impacts on the quality of tutorial process. It could support students learning in some aspects, however; it also reduce the quality of tutorial process. To minimise the negative effects, supporting factors should be optimised. Faculty should also consider other innovations that are more appropriate with Eastern culture and PBL characteristics.